A metabolic shift toward glycolysis enables cancer cells to maintain survival upon concomitant glutamine deprivation and V-ATPase inhibition - Lengauer, Florian; Geisslinger, Franz; Gabriel, Antje; von Schwarzenberg, Karin; Vollmar, Angelika M.; Bartel, Karin (Frontiers in Nutrition, 2023)
It is widely known that most cancer cells display an increased reliance on glutaminolysis to sustain proliferation and survival. Combining glutamine deprivation with additional anti-cancer therapies is an intensively investigated approach to increase therapeutic effectiveness. In this study, we examined a combination of glutamine deprivation by starvation or pharmacological tools, with the anti-cancer agent archazolid, an inhibitor of the lysosomal V-ATPase. We show that glutamine deprivation leads to lysosomal acidification and induction of pro-survival autophagy, which could be prevented by archazolid. Surprisingly, a combination of glutamine deprivation with archazolid did not lead to synergistic induction of cell death or reduction in proliferation. Investigating the underlying mechanisms revealed elevated expression and activity of amino acid transporters SLC1A5, SLC38A1 upon starvation, whereas archazolid had no additional effect. Furthermore, we found that the export of lysosomal glutamine derived from exogenous sources plays no role in the phenotype as knock-down of SLC38A7, the lysosomal glutamine exporter, could not increase V-ATPase inhibition-induced cell death or reduce proliferation. Analysis of the cellular metabolic phenotype revealed that glutamine deprivation led to a significant increase in glycolytic activity when V-ATPase function was inhibited concomitantly. This was confirmed by elevated glycolytic capacity and reserve key glycolytic enzymes, and an increase in hexokinase activity. Our study, therefore, provides evidence, that glutamine deprivation induces autophagy, which can be prevented by simultaneous inhibition of V-ATPase function. However, this does not lead to a therapeutic benefit, as cells are able to circumvent cell death and growth inhibition by a metabolic shift toward glycolysis.